Increased risk of complications in smokers undergoing reversal of diverting ileostomy. Issue 10 (31st May 2021) - Cribb, Benjamin; Kollias, Victoria; Hawkins, Rosalyn; Ganguly, Timothy; Edwards, Suzanne; Hewett, Peter
Abstract: Background: Diverting ileostomy (DI) is utilised in rectal cancer surgery to mitigate the effects of anastomotic leak. The aim of this study was to assess the clinical risk factors associated with post‐operative complications of DI reversal. Methods: A single‐centre retrospective analysis of patients who underwent surgical resection for rectal cancer and subsequent DI reversal between January 2012 and December 2020 was undertaken. Medical records were reviewed to extract clinical, operative and pathologic details and post‐operative complications according to the Clavien‐Dindo classification. Univariate and multivariable analyses were undertaken to assess risk factors associated with post‐operative complications of DI reversal. Results: One hundred and twenty‐six adult patients who underwent DI reversal were included of which 49 had a post‐operative complication (39%). The most common complication was prolonged post‐operative ileus, which occurred in 24 patients (19%). On multivariable analysis smoking was significantly associated with overall complications (odds ratio [OR] = 5.60, 95% confidence interval [CI] 1.90–16.52, p  = 0.0018), and high Clavien‐Dindo (2–5) category complications (OR = 4.60, 95% CI 1.81–11.68, p  = 0.0013). In addition, patients who received adjuvant chemotherapy were less likely to have a reversal of DI complication (OR = 0.43, 95% CI 0.19–0.94, p  = 0.0342) and less likely to have a high Clavien‐Dindo (2–5) category complication (OR = 0.44, 95% CI 0.20–0.93, p  = 0.0311). Conclusion: Smokers who have undergone surgical resection of rectal cancer have a significantly increased risk of post‐operative complications after DI reversal. In these patients, the importance of smoking cessation must be emphasised. The decreased complication rate observed in patients who received adjuvant chemotherapy was an unexpected finding. Abstract : A retrospective analysis of patients undergoing reversal of diverting loop ileostomy was conducted with significantly more post‐operative complications in smokers and less post‐operative complications in patients who had received adjuvant chemotherapy. No differences in post‐operative complications were identified with respect to delayed closure or type of anastomosis.